DESAIN DAN MODIFIKASI STRUKTUR SASIS KENDARAAN LISTRIK RODA TIGA UNTUK PENINGKATAN FAKTOR KEAMANAN MENGGUNAKAN METODE ELEMEN HINGGA - yayang permadi; Revvan Rifada Pradiza; Moh. Rizanto Juliarsyah (MULTITEK INDONESIA, 2025)
This study aims to design and evaluate the chassis structure of a three-wheeled electric vehicle with a focus on improving the factor of safety (FoS) through geometric and material modifications. A three-dimensional model was developed using SolidWorks, while numerical analysis was conducted with the finite element method in ANSYS Workbench. Static loading scenarios were applied in the range of 0–600 kg, with load points positioned at the driver and cargo sections. The initial design showed an FoS value of less than 1 under a 200 kg load, indicating that it did not meet the safety criteria. The first modification, involving the addition of a base plate and reinforcements to the front cross members, increased the FoS to 1.02. A second modification, which included material adjustments and reinforcement of the cargo base, further improved the FoS to 1.29 while reducing the maximum stress by up to 33% compared to the initial design. These findings highlight that a combination of structural reinforcement strategies and appropriate material selection can significantly enhance chassis performance and achieve an acceptable safety level.